2015
DOI: 10.1007/s11481-015-9617-x
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin, a Natural Flavonoid, Attenuates EAE Severity Through the Modulation of Dendritic Cell and Other Immune Cell Functions

Abstract: Apigenin, a natural flavonoid, found in several plants, fruits, vegetables, herbs, and spices, is known to have anti-oxidant and anti-inflammatory properties that are evident in the use of these substances for centuries as medicinal approaches to treat asthma, insomnia, Parkinson's disease, neuralgia, and shingles. However, there is a considerable dearth of information regarding its effect on immune cells, especially dendritic cells (DC) that maintain the critical balance between an immunogenic and tolerogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 44 publications
2
41
0
Order By: Relevance
“…Although we are the first to demonstrate that flavonoids can directly promote OPC maturation and remyelination, several flavonoids are reported to have neuroprotective activity as well as neuroimmunomodulatory activity (reviewed by Jaeger, Parylak, & Gage, ; Spagnuolo, Moccia, & Russo, ). Apigenin and hesperidin, for example, can both reduce neuroinflammation in rodents with experimental autoimmune encephalomyelitis, a model of MS (Ciftci et al, ; Ginwala et al, ; Haghmorad et al, ). Quercetin has neuroprotective activities following hypoxia (Pandey, Patnaik, Muresanu, Sharma, & Sharma, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although we are the first to demonstrate that flavonoids can directly promote OPC maturation and remyelination, several flavonoids are reported to have neuroprotective activity as well as neuroimmunomodulatory activity (reviewed by Jaeger, Parylak, & Gage, ; Spagnuolo, Moccia, & Russo, ). Apigenin and hesperidin, for example, can both reduce neuroinflammation in rodents with experimental autoimmune encephalomyelitis, a model of MS (Ciftci et al, ; Ginwala et al, ; Haghmorad et al, ). Quercetin has neuroprotective activities following hypoxia (Pandey, Patnaik, Muresanu, Sharma, & Sharma, ).…”
Section: Discussionmentioning
confidence: 99%
“…S3 treatment was able to improve OPC maturation in vitro in presence of HMW HA and to promote functional remyelination in the LPC-induced demyelination model [106], suggesting that selective hyaluronidase inhibitors can be exploited to foster endogenous remyelination following CNS injuries. Several flavonoids (i.e., apigenin and hesperidin) have been shown to exert neuroprotective and immunomodulatory activity in the EAE model [107,108], suggesting that flavonoids can be potentially used as therapeutic compounds to counteract dysfunctional processes causing demyelination.…”
Section: Hyaluronanmentioning
confidence: 99%
“…Flavones, such as hesperidin, apigenin, and luteolin, are present in herbs, fruits, and vegetables, like parsley, oregano, celery, citrus fruit, artichoke, and lettuce, of which the intake is typically low in a Western diet and high in a Mediterranean diet 141. These flavones effectively suppress disease progression in the EAE model 154, 157. Interestingly, it was recently demonstrated that flavonoids, such as scutellarin, promote CNS repair, as demonstrated in the cuprizone model, which is commonly used to study de‐ and remyelination 155, 156.…”
Section: Flavonoidsmentioning
confidence: 99%
“…141 progression in the EAE model. 154,157 Interestingly, it was recently demonstrated that flavonoids, such as scutellarin, promote CNS repair, as demonstrated in the cuprizone model, which is commonly used to study de-and remyelination. 155,156 This indicates that flavonoids may be useful not only to target the inflammatory response in MS but also to promote repair of damage within the CNS.…”
Section: Flavonoidsmentioning
confidence: 99%